Quality of Life in Elderly with Stress Urinary Incontinence at Elderly Posyandu Dempo Health Center Palembang - Namira Amalia; Amir Fauzi; Hadrians Kesuma Putra (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. Urinary incontinence is the loss of a person's ability to control urination. This condition is a common health problem that is often found in the elderly, especially in women. Stress urinary incontinence is one of the urinary incontinence that is often found due to increased intra-abdominal pressure. Urinary incontinence can have a negative effect on the quality of life of the elderly. This study aims to provide an overview of the quality of life in elderly women with stress urinary incontinence. Method. This study is observational descriptive research. The data was obtained from interviews with elderly women at the Elderly Posyandu Dempo Health Center Palembang in the period October – November 2022, who met the inclusion and exclusion criteria. Results. The samples in this study have more demographic characteristics of the elderly group at the age 60-69 years (70%), last education level in elementary school (47.5%), married (57.5%), and normal BMI (53.8%). This study found elderly women with a history of parity ≥ 2 (81.3%), and vaginal delivery (75%). It was found that elderly women with stress urinary incontinence had a moderate quality of life (82.5%) and moderate results in all domains of quality of life, namely physical health (46.3%), psychology (62.5%), social relations (53.7%), and the environment (62.5%). Conclusion. Elderly women with stress urinary incontinence at the Elderly Posyandu of the Dempo Palembang Health Center have a moderate quality of life and moderate impact on the domains of physical health, psychology, social relations, and the environment.